Evaluating the efficacy of biologics with and without methotrexate in the treatment of psoriatic arthritis: a network meta-analysis - Philip J Mease; Daniel E Furst; Jeffrey R Lisse; Christophe Sapin; Kirstin Griffing; Sarah Ross; Paulo Reis; Aisha Vadhariya; Soumya Reddy (RMD Open)
Introduction An important consideration in the treatment of patients with psoriatic arthritis (PsA) is whether the addition of methotrexate (MTX) to biologics has greater efficacy than biologic monotherapy with respect to efficacy outcomes in these patients.Objectives To conduct a network meta-analysis (NMA) comparing biologics by treatment class with and without MTX for treatment of adults with active PsA.Methods A systematic literature review (SLR) identified randomised, double-blinded, controlled trials, and a Bayesian NMA compared biologics with and without MTX by treatment class (tumour necrosis factor inhibitors (TNFi), interleukin-23 inhibitors (IL-23i) and IL-17i). Efficacy outcomes included American College of Rheumatology 20%, 50% and 70% (ACR20, ACR50 and ACR70) improvement response.Results The SLR initially identified 31 studies, of which 17 met feasibility criteria for the NMA by containing the ‘without MTX’ subgroup. For ACR20 efficacy (the most robust assessment examined), all active treatments were significantly better than placebo. No statistically significant differences were demonstrated between biologic monotherapy (for all classes examined) and biologics in combination with MTX for ACR20/50. IL-17i were comparable to IL-23i, and IL-17i were significantly better than TNFi for ACR20. Although limited by fewer trials, TNFi, IL-23i and IL-17i were not statistically different for ACR50/70.Conclusions Concomitant use of MTX and biologics did not improve ACR efficacy outcomes versus biologic monotherapy. MTX does not appear to be necessary as a background therapy when biologics are used for the achievement of ACR20/50 responses in patients with PsA.